Demystifying the Effect of High-Performance Work Systems on Job Involvement Based on Dual-Path Mediation Model - Aastha Tripathi; Aalok Kumar (American Business Review, 2023)
This study investigates the links between high-performance work systems (HPWS) and job involvement (JI) via organizational justice (OJ) and employee well-being (EW) as mediators. The proposed social exchange theory-based research framework is used to demystify the role of HPWS on job involvement. The proposed framework is validated with ten five-star hotels in India through structural equation modelling. The model reliability and robustness of constructs are tested with confirmatory factor analysis. The findings indicate that organizations must pay close attention to the perceptions of organizational justice and employee wellbeing to foster greater job involvement in their workforce. The positive relationship between HPWS and job involvement was found to be partially mediated by organizational justice and employee wellbeing. Further, HPWS showed a positive relationship with job involvement that was both direct and significant. The present research contributes to the existing body of literature by examining organizational justice and employee wellbeing as mediating variables between HPWS and job involvement in the Indian hotel industry.